Impacts of water resource development on hydrological connectivity of different floodplain habitats in a highly variable system. (20th February 2019) - Higgisson, William; Higgisson, Brian; Powell, Megan; Driver, Patrick; Dyer, Fiona
Abstract: Floodplains and their associated wetlands are important features of semiarid and arid landscapes, providing habitat and refugia for native species as well as contributing to human needs for freshwater. Globally, floodplain habitats are some of the most modified ecological communities because of water resource development and land‐use changes. However, the hydrological changes that have occurred in highly variable semiarid and arid systems are rarely quantified in a way that helps us understand the consequences for different floodplain habitat types. This study investigated changes in floodplain‐river connectivity that have occurred because of water resource development on four floodplain habitat types in the Lachlan River Catchment, Australia: (a) temporary floodplain lakes, (b) intermittent river red gum ( Eucalyptus camaldulensis ) swamps, (c) intermittent black box ( Eucalyptus largiflorens ) swamps, and (d) terminal wetlands (wetlands along distributary creeks). Changes to floodplain‐river connectivity characteristics were calculated using their commence to fill thresholds and flow scenarios derived from a river hydrology model, enabling comparison of long‐term data sets (120 years) encompassing a range of climate conditions. Connection regime metrics have changed significantly in all floodplain habitats except intermittent black box swamps. Temporary floodplain lakes have experienced the greatest reduction in number of connection events (60% reduction), followed by intermittent river red gum swamps (55% reduction). Intermittent black box swamps and terminal wetlands have experienced the least change in number of connection events (35% reduction). The nature of the change in connection suggests a change in vegetation communities will occur in response to long‐term hydrological change.